2008
DOI: 10.1152/ajpcell.00400.2007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the molecular chaperone oxygen-regulated protein 150 (ORP150) to mitochondria and its induction by cellular stress

Abstract: Arrington DD, Schnellmann RG. Targeting of the molecular chaperone oxygen-regulated protein 150 (ORP150) to mitochondria and its induction by cellular stress. Am J Physiol Cell Physiol 294: C641-C650, 2008. First published December 19, 2007 doi:10.1152/ajpcell.00400.2007 is an inducible endoplasmic reticulum (ER) chaperone molecule that is upregulated after numerous cellular insults and has a cytoprotective role in renal, neural, and cardiac models of ischemiareperfusion injury. ORP150 also has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…On the other hand, Arrington and Schnellmann [42] reported that SIRT1 attenuated the palmitate-induced ER stress via induction of ORP150 (oxygen-regulated protein 150) through forkhead box protein O (FOXO) 1a in HepG2 cells. FOXO1 is known to induce HO-1 expression by binding to HO-1 promoter [43].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Arrington and Schnellmann [42] reported that SIRT1 attenuated the palmitate-induced ER stress via induction of ORP150 (oxygen-regulated protein 150) through forkhead box protein O (FOXO) 1a in HepG2 cells. FOXO1 is known to induce HO-1 expression by binding to HO-1 promoter [43].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ER chaperone protein ORP150 protects ECs against ER stress-induced apoptosis [48,49]. ER stress induced by the accumulation of unfolded proteins in the ER is considered a survival pathway; however, prolonged or severe ER stress leads to programmed cell death via specific pathways originating from the ER [50].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HYOU1 localization was found not to be restricted to the ER. In rats, glycosylated HYOU1 was detected in mitochondria, and an N-terminally truncated form was found in the cytoplasm (98,99). Accordingly, we assume that HSP70G and its homologs may be localized to several cellular compartments as part of a multiple targeting strategy.…”
Section: Table I Relative Quantification Of the N-glycans Found On Ccmentioning
confidence: 93%